Is female circumcision evolving or dissolving in Norway? A qualitative study on attitudes toward the practice among young Somalis in the Oslo area - Gele AA; Sagbakken M; Kumar BN (Dove Medical Press, 2015)
Abdi A Gele,1,2 Mette Sagbakken,1,2 Bernadette Kumar2 1Department of Nursing and Health Promotion, Oslo and Akershus University College of Applied Sciences, Oslo, Norway; 2Norwegian Centre for Minority Health Research, Oslo, Norway Abstract: Female genital mutilation or female circumcision (FC) is increasingly visible on the global health and development agenda – both as a matter of social justice and equality for women and as a research priority. Norway is one of the global nations hosting a large number of immigrants from FC-practicing countries, the majority from Somalia. To help counteract this practice, Norway has adopted a multifaceted policy approach that employs one of the toughest measures against FC in the world. However, little is known about the impact of Norway’s approach on the attitudes toward the practice among traditional FC-practicing communities in Norway. Against this background, this qualitative study explores the attitudes toward FC among young Somalis between the ages of 16 to 22 living in the Oslo and Akershus regions of Norway. Findings indicate that young Somalis in the Oslo area have, to a large extent, changed their attitude toward the practice. This was shown by the participants’ support and sympathy toward criminalization of FC in Norway, which they believed was an important step toward saving young girls from the harmful consequences of FC. Most of the uncircumcised girls see their uncircumcised status as being normal, whereas they see circumcised girls as survivors of violence and injustice. Moreover, the fact that male participants prefer a marriage to uncircumcised girls is a strong condition for change, since if uncut girls are seen as marriageable then parents are unlikely to want to circumcise them. As newly arrived immigrants continue to have positive attitudes toward the practice, knowledge of FC should be integrated into introduction program classes that immigrants attend shortly after their residence permit is granted. This study adds to the knowledge of the process of the abandonment of FC among immigrants in Western countries. Keywords: FGM, immigrants, attitude change, Somalis